Spatial arrangement of stormwater infiltration affects partitioning of subsurface storage and baseflow timing - Choat, Benjamin, author; Bhaskar, Aditi, advisor; Bailey, Ryan, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2019)
Urban stormwater management is using distributed facilities that treat stormwater near where it falls at an increasing rate. These facilities are often designed to infiltrate water that would have previously been conveyed overland. By directing water that would have previously made it to receiving streams very quickly via overland flow into subsurface flow paths, the soil moisture, groundwater, and stream flow regimes are altered. While these alterations may have significant implications for urban watershed management, there remains a lack of knowledge about how spatial arrangements of infiltration focused facilities may affect catchment scale water-balances, including subsurface storage and streamflow. In particular, little focus has been given to relating site-scale behavior with catchment scale response. This project used a physically-based numerical model, ParFlow, to investigate the relationships between spatial arrangements of infiltration facilities, subsurface partitioning of water between unsaturated and saturated zones, and baseflow response duration and timing. Our findings show that more spatially distributed infiltration facilities, as compared to spatially-clustered infiltration facilities, encourage greater unsaturated zone storage, less saturated zone storage, and more total subsurface storage in scenarios where surface ponding is not severe. Depth to water table beneath infiltration facilities was found to be the main driver of observed differences in partitioning of subsurface storage. In our lowest conductivity soil, silt, severe groundwater mounding was observed at steady-state with significant surface ponding. In a catchment with high permeability and diffusivity, baseflow response to precipitation was delayed in the clustered infiltration scenario compared to the distributed scenario. The clustered scenario resulted in more baseflow after longer inter-event durations but lower baseflow between sequential precipitation events with short inter-event durations. In the same catchment, antecedent moisture was shown to amplify sensitivity of baseflow response to clustered infiltration spatial arrangement. These results can be used to help guide decisions about spatial locations of stormwater infiltration facilities to meet urban watershed management goals such as increasing plant available water, increasing aquifer recharge, producing more consistent or dynamic baseflow, and quicker or more delayed baseflow responses to precipitation.
Keywords: green infrastructure; stormwater infiltration; surface-subsurface interaction; ParFlow; baseflow; stormwater management